A Remote Controlled,Voice Assisted Navigation,Human Rescue and Home Fire Fighting Robot - Apoorva L Rao, Bhoomika D, Bhavyashree R, Brunda B and Dr. R.Venkata Siva Reddy (International Journal of Advanced Science and Technology, 2020)
Fire-fighting is an extremely hazardous job and     there are many risks involved for a fire-fighter. Using technology in the form of fire-fighting robots helps in preventing unnecessary loss of life by aiding fire-fighters in rescue operations, collecting data for scientific research, extinguishing fire, etc. This paper describes the development of a remotely controlled mobile robot for fighting home fires. It is equipped with sensors, camera, a container with water pump, gear motors for movement, Bluetooth module and an audio playback unit for communication. Using the live camera feed, a human in remote location can control the movement of the robot and deliver it to site of the fire disaster. Sensors like object detection sensor help in avoiding obstacles when the robot is moving. The robot moves smoothly to the disaster area, fire is located and high pressure water is discharged from the pump to put out the fire. All commands are issued to the robot through Bluetooth which makes it possible for remote communication. The whole system is controlled using PIC Microcontroller